Central African Economic and Monetary Community : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper assesses the appropriate level of international reserves for the Economic and Monetary Community of Central Africa. The management of the regional central bank's (BEAC's) international reserves is governed by monetary cooperation agreements with France. In view of current risks, it is suggested that the BEAC should define its target level of international reserves. The BEAC should have a framework that reflects fairly each member state's contribution to the pooled reserves. The enforcement of the surrender requirement should be based on a finding of noncompliance even if the target level is achieved. The institutional framework for reserve management should also provide for the achievement of the target level.